Lymphocytic gastritis - Puderecki, Michał; Wronecki, Lech; Cięszczyk, Katarzyna; Szumiło, Justyna (Polish Journal of Pathology, 2019)
Organic basis of gastrointestinal symptoms is in the scope of many specialists. In this article lymphocytic gastritis, relatively newly described and not widely-known entity is presented. The lesion is characterized by presence of numerous mature lymphocytes in the surface and foveolar epithelium, as well as lymphocytic infiltration of the lamina propria. According to the definition at least 25 lymphocytes per 100 gastric epithelial cells is now required for the diagnosis. Literature found in wide range of databases was searched for morphological features of lymphocytic gastritis and its relationship with others coexisting or predisposing conditions or lesions. A strong positive correlation between celiac disease and Helicobacter pylori infection, and occurrence and severity of lymphocytic gastritis was revealed. A relationship was also found between lymphocytic gastritis and gastric lymphomas and other conditions.